QUALITY MANAGEMENT AS A FACTOR SUSTAINABLE BUSINESS - LYUDMILA MIKHAILOVNA Kupriyanova (Мир новой экономики, 2018)
The article is devoted to quality control issues affecting the sustainable business development. Researched domestic and foreign experience of production quality management system, management functions (planning and organization of work, encouraging employees to work actively to ensure product quality, monitoring and evaluation of the quality of products, developing and implementing quality management activities). Given the desire to integrate into the world economy, entrepreneurs should focus on changing targets global vector of development in the field of quality management as the sources of development of the enterprise. The significance of developing a system of indicators for assessing industrial activities related to the need to monitor the effectiveness and reliability of functioning of the Organization to identify anomalies and development recommendations to address them. Concluded that the advantage of a systematic approach to quality management, which ensures improved consumer confidence inthe quality and safety of manufactured products, market expansion, attraction of foreign investors on investment, as well as improving the reputation of manufacturers of high-quality and bezopasnnoj products.